Boosting the Efficiency of CZTS/Si Tandem Solar Cells Using In2O3 Layer in CZTS Top Cell. Issue 8 (3rd July 2021) - Doumit, Nicole; Soro, Kahatie; Ozocak, Aylin; Batut, Nathalie; Schellmanns, Ambroise; Saintaime, Eddy; Ntsoenzok, Esidor
Abstract: While single‐junction solar cells may be capable of attaining AM1.5 theoretical efficiency of 33.16%, infinite multijunction (MJ, Tandem) solar cells will have a limiting efficiency of 86.8%. Tandem solar cells based on crystalline silicon (c‐Si) bottom cells are therefore attracting great interest. An interesting candidate for the top cell absorber is represented by copper zinc tin sulfide Cu2 ZnSnS4 (CZTS). In this work, the CZTS/Si tandem solar cell is optimized by using indium oxide / Cadmium sulfide (In2 O3 /CdS) hybrid buffer. This present work reports CZTS/Si solar cell with an open‐circuit voltage V OC of over 0.942 V and a J SC of 34.7 mA cm − ² by adding In2 O3 layer in the CZTS top cell. The added In2 O3 layer has a thickness of 0.022 µm and is n‐doped with a concentration of 1e20 cm −3 . Compared with a CZTS/Si in which the hybrid buffer is of CdS, the efficiency is increased from 13.5% to 28.4%. These hybrid In2 O3 /CdS buffers provide a promising way to reduce the V OC deficit and further boost the efficiency of CZTS/Si solar cells. Abstract : Copper zinc tin sulfide (CZTS) / Silicium (Si) solar cells are attracting great interest. In this work, a solar cell with an open‐circuit voltage of over 0.942 V and a short‐circuit current density of 34.7 mA/cm 2 is reported. The efficiency is increased to 28.4% when using indium oxide (In2 O3 ) layer. This provides a promising way to boost the efficiency of CZTS/Si solar cells.